Chapter 2 Getting everyone on the same page - von Thiele Schwarz, Ulrica (Taylor & Francis, 2018)
In designing, implementing, and evaluating organizational interventions, program logic plays a central role as it outlines the core components of the intervention and links them to both proximal and distal outcomes. Also, central in the design, implementation, and evaluation of organizational interventions is the engagement of stakeholders across the organization (employees, managers, and specialists). Concrete tools are lacking for stakeholders to be engaged in the design of interventions and in defining criteria that can guide evaluation. This chapter outlines a structured process – the cocreated program logic (COP) process – for how organizational stakeholders can be involved in defining intervention goals and activities and thus forming the program logic together with interventionists (researchers or consultants). The program logic can then be used to guide the evaluation of the organizational intervention. The authors present two cases illustrating how the COP process has been used in their reserach. The chapter ends with lessons learned.